Cow and calf performances as affected by fertilizing and burning bluestem pastures - R.R. Schalles; L.H. Harbers; E.F. Smith; Clenton E. Owensby; Don Boggs (Kansas Agricultural Experiment Station Research Reports, 1976)
Burning and fertilizing Bluestem pastures were evaluated by comparing performances of spring-calving cows and calves that grazed them. Two control-pastures were not burned or fertilized; two pastures were burned; and two were burned and fertilized with 40 pounds of nitrogen an acre, applied aerially. Neither average daily gains or the calves nor reproductive performance of the cows differed significantly among treatments, but more pounds of calf were weaned per acre from pastures burned and fertilized.
Keywords: Cattlemen' s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Performance; Fertilizer; Weaning